Pengaruh Kemudahan Transaksi QRIS dan Harga Terhadap Keputusan Pembelian pada UMKM (Studi Kasus Kedai Bakso Laladana) di Cikarang Utara - Arla Mutiara Fazira; Robby Irvawan (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. The development of digital technology has encouraged changes in payment system across business sectors, including Micro, Small, and Medium Enterprises (MSMEs). One of the digital payment innovations widely used is the Quick Response Code Indonesian Standard (QRIS). In addition to transaction convenience, price is also an important factor considered by consumers when making purchasing decisions. However, in practice, some consumers still prefer other payment methods and have various considerations regarding the prices offered. These conditions may influence consumer purchasing decisions. This study aims to determine the effect of QRIS Transaction Ease and Price on Purchaing Decisions at Kedai Bakso Laladana in North Cikarang. This study employed a quantitative approach with descriptive research methods. The population consisted off all consumers of Kedai Bakso Laladana. The sample was selected using a no-probability sampling technique with a purposive sampling method involving 96 respondents. Data were analyzed using multiple liniear regression with IBM SPSS statistics 27. The result indicate that QRIS Transaction Ease has a positive and significant effect on Purchasing Decisions by 43,4%, while price has a positive and significant effect on Purchasing Decisions by 47, 4%. Simultaneosly , QRIS Transaction Ease and Price have a positive and significant effect on Purchasing Decision by 52%, qhilw the remaining 48% is influenced by other variables not exaimined in this study. Keywords: QRIS Transaction Ease, Price, Purchasing Decisions.